Toxoplasma gondii infection in meat animals from Africa: Systematic review and meta-analysis of sero-epidemiological studies - TONOUHEWA, ARETAS; AKPO, YAO; SESSOU, PHILIPPE; ADOLIGBE, CAMUS; YESSINOU, R. ERIC; HOUNMANOU, YAOVI GILDAS; ASSOGBA, MARC NAPOLÉON; YOUSSAO ABDOU KARIM, ISSAKA; FAROUGOU, SOUAÏBOU (My University, 2017)
Aim: Toxoplasma gondii is an ubiquitous apicomplexan parasite which causes toxoplasmosis in humans and animals. Felids especially cats are definitive hosts and almost all warm-blooded mammals, including livestock and human can serve as intermediate hosts. Food animals can be reservoirs for T. gondii and act as one of the sources for parasite transmission to humans. The objective of this study is to collect serological data on the prevalence of anti-T. gondii antibody, and risk factors for certain food animals from Africa to provide a quantitative estimate of T. gondii infection among these species from different African countries. Materials and Methods: Four databases were used to search seroepidemiological data on the prevalence of anti-T. gondii antibody in food animals between 1969 and 2016 from African countries. The search focused on data obtained by serologic test in food animals and meta-analyses were performed per species. Results: A total of 30,742 individual samples from 24 countries, described in 68 articles were studied. The overall estimated prevalence for toxoplasmosis in chicken, camel, cattle, sheep, goat, pig were 37.4% (29.2-46.0%), 36% (18-56%), 12% (8-17%), 26.1% (17.0-37.0%), 22.9% (12.3-36.0%), and 26.0% (20-32.0%), respectively. Moreover, major risk factor of infection was age, farming system, and farm location. Conclusions: A significant variation in the seroepidemiological data was observed within each species and country. The results can aid in an updated epidemiological analysis but also can be used as an important input in quantitative microbial risk assessment models. Further studies are required for a better and continual evaluation of the occurrence of this zoonotic infection
Keywords: animal health; meta-analysis; Toxoplasmosis; zoonosis